2015
DOI: 10.1158/1940-6207.capr-14-0380
|View full text |Cite
|
Sign up to set email alerts
|

Improved Innate Immune Responses by Frondanol A5, a Sea Cucumber Extract, Prevent Intestinal Tumorigenesis

Abstract: Sea cucumbers are a source of anti-bacterial, anti-inflammatory, and anti-cancer compounds. We show that sea cucumber extract Frondanol® A5 is capable of enhancing innate immune responses and inhibiting intestinal tumors in APCMin/+ mice. APCMin/+ mice were fed semi-purified diets containing 0, 250, or 500 ppm Frondanol®A5 for 14 weeks before we assessed intestinal tumor inhibition. Dietary Frondanol® A5 suppressed small intestinal polyp sizes and formation up to 30% (p<0.02) in males and up to 50% (p<0.01) in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Based on the literature suggested that existing glycosaminoglycan content in sea cucumbers may play a role as a modulator of inflammation such as macrophage, become more active. 10 Glycosaminoglycans (GAGs) in gold sea cucumber, participate in a variety of biological processes including cell-matrix interactions and activation of chemokines, enzymes and growth factors. 11 There are a variety of growth factors in the extracellular matrix (ECM), including members of the transforming growth factor-beta (TGF-β) superfamily, and vascular endothelial growth factor (VEGF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature suggested that existing glycosaminoglycan content in sea cucumbers may play a role as a modulator of inflammation such as macrophage, become more active. 10 Glycosaminoglycans (GAGs) in gold sea cucumber, participate in a variety of biological processes including cell-matrix interactions and activation of chemokines, enzymes and growth factors. 11 There are a variety of growth factors in the extracellular matrix (ECM), including members of the transforming growth factor-beta (TGF-β) superfamily, and vascular endothelial growth factor (VEGF).…”
Section: Discussionmentioning
confidence: 99%
“…The release of TGF-β led to an increase in collagen synthesis. 10 The process of wound healing will occur faster, and clinically can be shown by the decrease of ulcer diameter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ds-echinoside A has also been shown to inhibit proliferation of human hepatocellular carcinoma cells, and to suppress cell adhesion, migration, invasion, and angiogenesis via regulation of MMP9, TIMP-1, and VEGF expression (65). Frondanol A5 is an isopropyl alcohol/water extract derived from Cucumaria frondosa and its application has been shown to inhibit cell growth via modulation of p21WAF1/CIP and Cdc25c, thus inducing apoptosis of human colon cancer cells (66), as well as innate immune responses and inhibiting the growth of intestinal tumors in mice model (67). Frondanol A5P, a polar extract isolated from Cucumaria frondosa.…”
Section: The Inhibitory Effects Of Echinoside a Ds-echinoside A Fromentioning
confidence: 99%
“…In female mice, both doses produced 80% inhibition of CTs. We reported an increase in immune responses in treated animals, in which the isolated macrophages showed increased phagocytosis and GILT expression, compared with untreated animals [ 31 ] ( Table 1 ) ( Figure 3 ). These data suggest that Frondanol A5 has the potential to improve innate immune responses during intestinal tumor formation and could be further developed for prevention and treatment.…”
Section: Immunostimulatory and Anti-tumor Functions Of Sea Cucumbementioning
confidence: 99%
“…Sea cucumbers consist of vitamins, minerals, cerebrocides, peptides, and lectins, and also contain unique molecules, such as sulfated polysaccharides, 12-methyltetradecanoic acid (12-MTA), philinopside E, triterpene glycoside compounds, glycosaminoglycan, and chondroitin sulfates [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In sufficient quantities, these unique compounds are known to possess anti-microbial, anti-oxidant, anti-angiogenic, anti-inflammatory, immunomodulatory, and anti-tumoral properties [ 28 , 29 , 30 , 31 ] ( Figure 1 ). As supplements, these sea cucumber extracts have been shown to suppress inflammation and increase innate immune responses.…”
Section: Introductionmentioning
confidence: 99%